MATEC Web of Conferences - Ibatov; Mekhtiyev Specialist in the field of electronics Senior researcher of Tomsk Polytechnic University, Candidate of technical sciences; Bulatbayev; Yakupova (2018)
In the article results of researches of brake devices of lifting machines UD of joint-stock company "ArcelorMittal Temirtau" are resulted. Defects were revealed as a result of the examination. A method and device for the unconditional control of defects and technical condition of the hinged joints of brake devices is developed in terms of the gap size and the angle of rotation between the links of the kinematic pairs "Widget-finger". For the monitoring of gaps, capacitive sensors are installed, mounted on hinged joints. It is substantiated that with the use of capacitive sensors it is possible to control the gaps in the hinged joints in real time. A device has been developed that makes it possible to estimate the magnitude of the gap at several points of the kinematic chain of the mechanism simultaneously.